2007
DOI: 10.1177/1077558707308754
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Nursing Home Hospitalization

Abstract: Hospitalization of nursing home residents is costly and potentially exposes residents to iatrogenic disease and psychological harm. This article critically reviews the association between the decision to hospitalize and factors related to the residents' welfare and preferences, the providers' attitudes, and the financial implications of hospitalization. Regarding the resident's welfare, factors associated with hospitalization included sociodemographics, health characteristics, nurse staffing, the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
237
5
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(258 citation statements)
references
References 79 publications
(215 reference statements)
10
237
5
6
Order By: Relevance
“…These concerns are highlighted in the international literature, but solutions are elusive. 9,10 Participants placed considerable weight on the views of patients and relatives, but there was relatively little mention of detailed advance care planning despite its advocacy in the UK, 17,21 the US, 18 and Australia. 16 The concept of a palliative care approach in nursing homes, as previously highlighted in other published research, [13][14][15] was implicit in many of the responses; a few responders described experiences of admission avoidance initiatives suggesting that, as outlined by Partridge, 29 a more proactive approach to avoid residents being sent to Funding Wessex Primary Care Network.…”
Section: 26mentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns are highlighted in the international literature, but solutions are elusive. 9,10 Participants placed considerable weight on the views of patients and relatives, but there was relatively little mention of detailed advance care planning despite its advocacy in the UK, 17,21 the US, 18 and Australia. 16 The concept of a palliative care approach in nursing homes, as previously highlighted in other published research, [13][14][15] was implicit in many of the responses; a few responders described experiences of admission avoidance initiatives suggesting that, as outlined by Partridge, 29 a more proactive approach to avoid residents being sent to Funding Wessex Primary Care Network.…”
Section: 26mentioning
confidence: 99%
“…1 There has been a widespread concern that some hospital admissions from nursing homes are 'inappropriate' or 'avoidable' [2][3][4][5][6][7][8] although there is little consensus about which admissions are avoidable. 9 It is unclear how admission decisions are made and what the key influencing factors are. Improvements in nursing home staffing levels, hospital discharge procedures and clinical care may reduce hospital admissions from long-term care facilities in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated that a variety of factors are associated with hospitalization of NH residents, ranging from state Medicaid bed-hold policies to availability of registered nurses and NPs to overall quality of care provided in the NH. [15][16][17][18] Examination of the factors rated by the expert panel in the current project provides insight into how potentially avoidable hospitalizations might be classified and the types of interventions that might be helpful in reducing these hospitalizations. Hospitalizations rated as potentially avoidable in this project highlight the need for better quality of care in identifying and assessing acute changes in resident condition with the availability and expertise of registered nurses and primary care clinicians for assessing acute changes in condition; better access to services such as laboratory, X-ray, and intravenous fluid administration; and greater focus on advance care planning as a strategy to reduce futile care, including education of residents and families, encouragement to complete a durable power of attorney for health care, and limits on the use of interventions such as hospitalization of residents who are unlikely to benefit.…”
mentioning
confidence: 99%
“…[1][2][3] Empirical research suggests that both the quantity and type of nursing home staff members, especially physicians, might have an impact on the number of potentially avoidable hospitalizations. 4 In particular, the lack of physicians at many nursing homes during off hours might be one cause of inappropriate hospitalizations. 5 If a medical issue arises during the evening or weekend that cannot be addressed over the phone, the on-call physician can either travel to the facility or recommend that the nursing home resident be transferred to a hospital.…”
mentioning
confidence: 99%